2017
DOI: 10.1016/j.jpain.2016.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Testing Assumptions in Human Pain Models: Psychophysical Differences Between First and Second Pain

Abstract: Acute pain arises from activation of myelinated (A delta) and unmyelinated (C) nociceptive afferents, leading to 1st (A-fiber) or 2nd (C-fiber) pain sensations. The current study sought to investigate first and second pain within glabrous and hairy skin sites in human upper-limbs. Fifty healthy adults (25 males/25 females, 18-30 yrs: mean = 20.5 ± 1.4) participated in a psychophysical study investigating electronically rated, thermal first and second pain sensations within the glabrous skin at the palm and hai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…However, employing the use of temperature optimization for testing may in effect eliminate the ability to detect site differences as theoretically expected. Importantly, the lack of a site difference in the current study is also consistent with our earlier study where site differences were found between the palm and forearm for the temperature for first pain threshold but not second pain threshold[5]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, employing the use of temperature optimization for testing may in effect eliminate the ability to detect site differences as theoretically expected. Importantly, the lack of a site difference in the current study is also consistent with our earlier study where site differences were found between the palm and forearm for the temperature for first pain threshold but not second pain threshold[5]. …”
Section: Discussionsupporting
confidence: 92%
“…; e.g., at the end of each ISI right before the next stimulation) (see Figure 1e) 27 . A similar analysis protocol has been determined effective and used in previous publications[5]. The TESS makes a single recording of thermode temperature and eVAS rating per contact at a preprogramed time point and was set to record at the same time interval as the Pathway.…”
Section: Methodsmentioning
confidence: 99%
“…The greater transparency of the skin would allow the thermal energy of the Nd:YAP laser to be deposited adjacent to the nociceptors located underneath the thick corneous layer of glabrous skin, rather than being absorbed in the most superficial layers of the skin as done by CO2 lasers and contact thermodes. This explanation is also supported by recent evidence that showed that the threshold for first pain elicited by a contact thermode was significant higher in the glabrous skin as compared to the hairy skin (Eckert et al, 2017). In addition, other studies have demonstrated differences in the latencies of laser-evoked brain potentials (LEPs) elicited by CO2 and Nd:YAP laser pulses applied onto the hairy skin (Cruccu et al, 2008), as well as between the latencies of LEPs and contact heat-evoked potentials (CHEPs) (Iannetti et al, 2006).…”
Section: Introductionsupporting
confidence: 76%
“…Noxious stimuli may cause simultaneous activation of Aδ and C fibres of skin nociceptors, giving rise to two different sensations of pain: the earliest sensation (first pain) is of sharp, stinging quality, while the latest (second pain) is of dull, burning quality (Eckert et al, 2017; Ploner et al, 2002; Price & Dubner, 1977). Probably, these two types of sensation relate also to two different processes occurring when a tonic noxious temperature stimulus is applied: adaptation and sensitization.…”
Section: Discussionmentioning
confidence: 99%